2008
DOI: 10.1007/bf03191115
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant-induced changes on antibiotic concentrations in the serum and bones

Abstract: The aim of this study was to determine whether the co-administration of acenocoumarin as anticoagulant and certain quinolones, i.e., cefapirin, pefloxacin and ciprofloxacin increased the levels of the given antibiotics and whether this resulted in a prolongation of prothrombin time. Seventy male albino Wistar rats aged 8-10 weeks and weighed 170 +/- 14 g were used and divided into seven groups (I, II, III, IV, V, VI, VII: n=10). The rats in group I received cefapirin via 1 g/kg/8h im injection. Group II receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…In these same studies, acenocoumarin coadministration significantly enhanced the serum concentrations of both quinolones and their penetration into mandibular bone but not femur. The mechanism of this effect is unknown [198]. However, case reports have documented quinolone-associated increases in PT/INR in patients receiving warfarin concurrently with ciprofloxacin, ofloxacin, norfloxacin, gatifloxacin, levofloxacin, and moxifloxacin [199][200][201][202][203][204][205][206][207][208][209][210][211][212][213][214].…”
Section: Metabolism Interactionsmentioning
confidence: 98%
See 1 more Smart Citation
“…In these same studies, acenocoumarin coadministration significantly enhanced the serum concentrations of both quinolones and their penetration into mandibular bone but not femur. The mechanism of this effect is unknown [198]. However, case reports have documented quinolone-associated increases in PT/INR in patients receiving warfarin concurrently with ciprofloxacin, ofloxacin, norfloxacin, gatifloxacin, levofloxacin, and moxifloxacin [199][200][201][202][203][204][205][206][207][208][209][210][211][212][213][214].…”
Section: Metabolism Interactionsmentioning
confidence: 98%
“…In addition, levofloxacin, norfloxacin, temafloxacin, trovafloxacin, grepafloxacin, moxifloxacin, gemifloxacin, sparfloxacin, and ciprofloxacin have been shown not to potentiate the anticoagulant effect of warfarin in healthy subjects and patients requiring long-term anticoagulation [163,[187][188][189][190][191][192][193][194][195][196][197]. Based on rat studies, ciprofloxacin and pefloxacin significantly increased prothrombin time (PT)/ international normalized ratio (INR) results after acenocoumarin administration [198]. These results need to be validated in humans.…”
Section: Metabolism Interactionsmentioning
confidence: 99%
“…Although drug displacement interactions (DDIs) can affect the absorption and drug distribution processes, the most clinically significant interactions, especially during antiinfective treatment, concern the elimination phase. Kotsiou et al (2008) investigated the simultaneous administration of cefapirin and acenocoumarin and observed that a prolongation of prothrombin time in the presence of cefapirin has been observed. It is known that a series of cephalosporin antibiotics (e.g., moxalactam, cefamandole, and cefaperazone), with Nmethyltetrazolethiol (NMTT), thiadiazolethiol (TDT), or methylthiadiazolethiol (MTDT) side chains in position 3 of the cephalosporin nucleus, cause vitamin K-responsive hypoprothrombinemia and bleeding in patients who are malnourished, physically weak, and/or elderly (Creedon and Suttie, 1986).…”
Section: Drug Displacement Interactions (Ddis)mentioning
confidence: 99%